Preparation of Li2-3xAlxS for All-Solid-State Li-S Battery - Phuc, Nguyen Huu Huy; Takaki, Maeda; Hiroyuki, Muto; Atsunori, Matsuda (Frontiers in Energy Research, 2021)
Li2-3xAlxS (0 ≤ x ≤ 0.1667) was prepared via the planetary ball-milling method. Diffuse reflection UV-Vis measurements revealed that the band gap and electronic structure of Li2S changed with the formation of defective Li2-3xAlxS. Compared with x = 0, the ionic conductivity for the sample with x = 0.1334 improved by ~3 orders of magnitude. The lithium movement activation energy and pre-exponential factor A were found to be dependent on the x value. Compared with Li2S, a ~10-fold improvement in the electronic conductivity was realized with Al2S3 addition. Additionally, the all-solid-state Li-S battery cell performance also displayed an enhancement in both the initial capacity and stability for sample x = 0.1667 compared with x = 0. This study highlighted the importance of the intrinsic electronic conductivity of the active materials (but not the electrode) on the performance of the all-solid-state Li-S battery.